Natural History of Patients with Typical and Atypical Catecholaminergic Polymorphic Ventricular Tachycardia. (3rd October 2022) - Trancuccio, A; Mazzanti, A; Kukavica, D; Giannini, G; Memmi, M; Gambelli, P; Bloise, R; Marino, M; Morini, M; Ortiz-Genga, M; Napolitano, C; Priori, S G
Abstract: Background: Recently, a novel genetic-based classification for Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) has been proposed to distinguish "typical" (RYR2 and CASQ2 genes) and "atypical" (TRDN, TECRL, CALM1–3, RYR2 loss-of-function [RYR2-LoF]) CPVT variants. Although some genetic forms were reported as malignant forms of CPVT, natural history data comparing typical and atypical CPVT variants are lacking. Purpose: We compared the natural history of "typical" and "atypical" forms of CPVT in a large cohort of patients with genetically confirmed CPVT. Methods: CPVT was diagnosed according to the criteria defined in the 2015 European Society of Cardiology Guidelines. Based on the genetic background, we classified the patients in two groups: 1) "Typical" CPVT (i.e., carriers of pathogenic or likely pathogenic mutations in RYR2 and CASQ2 genes); 2) "Atypical" CPVT (i.e., carriers of pathogenic or likely pathogenic mutations in TRDN, TECRL, CALM1–3 and RYR2-LoF). Patients with mutations in the CALM1, CALM2 or CALM3 were not identified in our cohort. The outcome was the occurrence of a life-threatening arrhythmic event (LAE), defined as: sudden cardiac death, aborted cardiac arrest or hemodynamically non-tolerated ventricular tachycardia. The Kaplan-Meier life-table method was used to determine the cumulative probability of experiencing a first LAE before the age of 40 years and in the absence of treatment. Outcomes in two groups were compared using the log-rank test. Results: The study cohort included 238 patients (56% females, median age at diagnosis 14 years [IQR: 9–28 years]), of whom 226/238 (95%) patients with "typical" CPVT (216 RYR2, 10 CASQ2), and 12/238 (5%) patients with "atypical" CPVT (5 RYR2-LoF, 4 TRDN, 3 TECRL). In the entire population, the cumulative probability of experiencing a first LAE between birth and the diagnosis of CPVT was 2.3%, 21.2 and 40.8% at 5, 20, and 40 years, respectively. At any given age, the probability of a first LAE in the absence of therapy was significantly higher in patients with atypical CPVT (25%, 36%, and 100% at 5, 20, and 40 years, respectively), as compared to patients with typical CPVT (1%, 20%, and 39% at 5, 20, and 40 years, respectively; p=0.003, Figure 1). Patients with atypical CPVT suffered LAEs in early childhood (i.e., by the age of 5 years) significantly more often than patients with typical CPVT (3/5 patients [60%] in atypical CPVT vs. 2/43 patients [5%] in typical CPVT, p<0.001; Figure 2). Conclusions: The natural history of CPVT is modulated by the genetic cause. Atypical CPVT variants are rare but are characterized by a worse outcome and a greater likelihood of experiencing an LAE since the early childhood, as compared to typical CPVT. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ricerca Corrente funding scheme of the Italian Ministry of Health